The metallogeny of the Upington and Kenhardt area, northern Cape - Boelema, Robert (Rhodes University, Faculty of Science, Department of Geology, 1995)
In the Upington region, there are three major- tectonic crustal provinces; namely the Kaapvaal Craton, Kheis and Namaqua tectonic provinces. The Eburnian-aged (early Proterozoic) Kheis Province developed along the western flank of the Archaean Kaapvaal Craton while the Kibaran-aged (middle Proterozoic) Namaqua Metamorphic Province, superimposed on the Eburnian-aged basement, developed to the east of the Kheis Province. The Namaqua Metamorphic Province is divided into the Gordonia and Bushmanland Subprovinces, the former being further subdivided into various tectonostratigraphic terranes. These are termed, from west to east, the Kakamas, Areachap, and Upington Terranes. The Upington Terrane includes fault bounded grabens with accompanied bimodal volcanism and sedimentation of the Wilgenhoutsdrif and Koras Groups. The Areachap Terrane consists predominantly of amphibolites generated in an island arc environment while the Kakamas Terrane is characterised by volcano-sedimentary sequences which have been extensively intruded by syn to late-tectonic predominantly I-type Keimoes Suite granitoids. The main styles of mineralisation correlate well with the various tectonostratigraphic terranes. Sedimentary exhalative massive sulphide deposits are characteristic of the Bushmanland Subprovince and are thought to be associated with the deposits at Aggeneys and Putsberg to the west of the area under investigation. These deposits are considered to have been deposited in an east-west-elongated intracontinental basin. The Kakamas Terrane is typified by granite-related mineralisation. In the eastern portion of the Kakamas Terrane, Sn-Wand base metal-bearing veins occur while pegmatites are developed in the western portion. These two styles of granite-related mineralisation is considered to reflect differing depths of formation due mainly to varying degrees of thrusting. The Areachap Terrane consists of volcanogenic massive sulphide deposits of the Besshi-type and is considered to have formed in a back-arc environment. In the Upington Terrane, the Wilgenhoutsdrif and Koras Groups consists essentially of minor Cu occurrences mainly disseminated within basalts and in structural trap sites. The possibility for sediment-hosted Cu deposits is not ruled out. More recent surface processes have led to uranium and gypsum deposits in pans, river beds and calcretes. Eburnian aged tectonic setting remains enigmatic. Kibaran-aged tectonics which best fits the metallogeny of the area under investigation is considered to be of a subduction zone from west to east formed by the collision of the Bushmanland "microcontinent" against the Kaapvaal Craton. Subduction fbrmed an island arc setting in which the massive sulphide deposits were formed in the Areachap Terrane while the Wilgenhoutsdrif Groups developed in a marginal basin. Further convergence led to collision of the two continents and underriding of the Bushmanland "microcontinent" which generated predominantly I-type granitoids represented by the Keimoes Suite. The level of emplacement of these granitoids is a reflection of the degree of foreland thrusting and produced shallower level Sn-W and base metal vein-type mineralisation closer to the suture zone and deeper level pegmatites further from the suture zone to the west. The final period of deformation is represented by northward lateral movement which created "pull apart" fault-bounded basins into which the Koras Group was deposited.
Keywords: Metallogeny -- South Africa; Metallogeny -- South Africa -- Northern Cape; Plate tectonics -- South Africa -- Northern Cape; Geology, Structural -- South Africa -- Northern Cape